2020
DOI: 10.3390/ma13010251
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Waste Polysilicon Sludge in Concrete

Abstract: Increasing use of cement in the construction industry is causing an alarming increase in carbon dioxide (CO2) emissions, which is a serious environmental threat, it can be reduced by the addition of supplementary cementitious materials (SCMs). The commonly used SCMs like ground granulated blast furnace slag (GGBS), metakaolin (MK) and fly ash (FA) have been successfully used to replace the cement partially or completely. Polysilicon sludge obtained from the photovoltaic industry is also a type of waste materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…Another study showed the decrease in compressive strength of concrete when cement was replaced with dried sewage sludge [26]. Incorporating the waste polysilicon sludge in concrete up to 20% replacement level resulted in the increase in compressive strength after 28 days of curing period [27]. The amounts of both dry and wet waste water sludge can be used up to 15% as an additive without causing considerable reduction in concrete compressive strength, because of the fact that sludge acts as filler materials responsible for improving the mechanical properties of concrete mix [28].…”
Section: Wykorzystanie Odpadów Szlamowych Z Dżinsu Tekstylnego W Zast...mentioning
confidence: 99%
“…Another study showed the decrease in compressive strength of concrete when cement was replaced with dried sewage sludge [26]. Incorporating the waste polysilicon sludge in concrete up to 20% replacement level resulted in the increase in compressive strength after 28 days of curing period [27]. The amounts of both dry and wet waste water sludge can be used up to 15% as an additive without causing considerable reduction in concrete compressive strength, because of the fact that sludge acts as filler materials responsible for improving the mechanical properties of concrete mix [28].…”
Section: Wykorzystanie Odpadów Szlamowych Z Dżinsu Tekstylnego W Zast...mentioning
confidence: 99%
“…Em alguns casos como na incorporação de lodo de papel, a considerável atividade pozolânica do material proporciona um refinamento da microestrutura e permite que os concretos com resíduo obtenham maiores resistências à penetração dos íons cloreto [79], comportamento não constatado nos concretos com lodo de produtos de limpeza. Materiais suplementares contendo alumínio em sua composição também podem ser capazes de adsorver os íons de cloreto para formais sais, reduzindo a quantidade de íons livres na estrutura de poros e consequentemente a taxa de penetração desse agente em concretos [80].…”
Section: Análise De Durabilidadeunclassified